Prevalence of functional dependence among elderly people - Gázquez Linares, José Jesús; Pérez Fuentes, María del Carmen; Mercader Rubio, María Isabel; Molero Jurado, María del Mar (Anales de Psicología / Annals of Psychology, 2011)
The most immediate consequence of aging is the dependent population growth. For this purpose, the aim of this study is to show the prevalence of dependence on basic and instrumental activities of daily living among the population older than 60 years old, depending on the gender, the marital status and the age, in a total sample of 1.222 people. The dependency level is higher among women, in nearly all basic activities, being the widow people who have shown the highest average dependency rate and for both, basic and instrumental activities. We have observed that there is a positive correlation between the increase of aging and the increase of dependence, except in the basic activity of eating. We can know the groups and features of dependant people, so it leads us, not only to estimate the resources needed to assist them but also the possibility of carrying out preventive work among those groups.